2015
DOI: 10.1063/1.4932133
|View full text |Cite
|
Sign up to set email alerts
|

Three-terminal graphene single-electron transistor fabricated using feedback-controlled electroburning

Abstract: We report room-temperature Coulomb blockade in a single layer graphene three-terminal singleelectron transistor (SET) fabricated using feedback-controlled electroburning. The small separation between the side gate electrode and the graphene quantum dot results in a gate coupling up to 3 times larger compared to the value found for the back gate electrode. This allows for an effective tuning between the conductive and Coulomb blocked state using a small side gate voltage of about 1V. The technique can potential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 23 publications
(23 reference statements)
0
25
0
Order By: Relevance
“…However, because of the erratic nature of the electroburning process, improving the reproducibility and reliability of such devices is a major challenge for future applications. To address this issue, researchers have first shown that the nanogap width could be tuned by varying the air pressure or by feedback controlled electroburning . The path taken by the crack is a second aspect to consider.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the erratic nature of the electroburning process, improving the reproducibility and reliability of such devices is a major challenge for future applications. To address this issue, researchers have first shown that the nanogap width could be tuned by varying the air pressure or by feedback controlled electroburning . The path taken by the crack is a second aspect to consider.…”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, researchers have first shown that the nanogap width could be tuned by varying the air pressure [21] or by feedback controlled electroburning. [2,13,[22][23][24][25][26][27] The path taken by the crack is a second aspect to consider. To tackle this issue, researchers generally use an "hourglass" design to create a constriction in the graphene flake where the current density is higher.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, phase change materials can be introduced in the nanogap to make electronic switches [145]. Because the nanogaps can be a few nanometers wide, single molecules can also be inserted to make transistors [71,109,[146][147][148][149][150][151][152][153][154], DNA sequencers [155,156] or quantum dots [74,157] hence making graphene nanogap systems extremely important in the field of molecular electronics.…”
Section: Motivationmentioning
confidence: 99%
“…However, because of the erratic nature of the electro-burning process, improving the reproducibility and reliability of such devices is a significant challenge for future applications. To address this issue, researchers have first shown that the nano-gap width could be tuned by varying the air pressure [75] or by feedback controlled electro-burning [8,71,73,[109][110][111][112]161]. The path taken by the crack is a second aspect to consider.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation